ANALISIS PENGEMBANGAN BISNIS MADU PADA CV ATH-THOIFAH DENGAN PENDEKATAN BUSINESS MODEL CANVAS - Rezki Kamila; Rizal Syarief; Imam Teguh Saptono (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2017)
Honey has many benefits not only as a medicine but also can be used as a food supplement. The market opportunities for honey business is still very wide open, this is indicated by the high value of Indonesian honey imports compared to the export value. Seeing these market conditions is one of the fundamental things established of CV Ath-Thoifah, si one of the company that develops traditional herbal products in Indonesia and basically using honey as the main ingredients of its products. The aims of this study are identifying business model canvas, determining the priority elements on business model canvas that will be developed, composing business model canvas improvement, and preparing alternative strategy to develop business of CV Ath-Thoifah. The respondents in this study are from internal and external team. The processing and data analysis utilize the qualitative method, identification of the current business model canvas, determination the priority elements to be developed use importance performance analysis method, SWOT analysis, and designing alternative business strategy. The results show nine elements of business model canvas in CV Ath-Thoifah now. Key activities, key partnership, and cost structure are the priority elements that will be developed. Based on the results of SWOT analysis and FGD, the alternative strategies can be coclude: 1) developing business in big cities outside Jabodetabek area, 2) adding distributors and agents intensively, 3) establishing special partnership in information technology (IT), 4) applying Good Manufacturing Practices (GMP) principles and BPOM certification, 4) increasing the allocation of funds in research and development field.